Avaliação da disponibilidade de fósforo em fertilizantes encapsulados - Costa, Cibeli Lira (2021)
The concentration of gradient diffusion was used as a passive sampling technique to mimic the physicochemical adsorption of P by plant roots. For this purpose, a binding gel was synthesized from agarose, polyacrylamide, and anionic resin. The validation tests of the synthesized binding gel showed homogeneity and resistance to handling, linear binding capacity, up to 50 mg P L-1 eluted with acidic solutions, elution factor close to 1.0, and costs equivalent to 2% of the commercial binding gel that employs ferrihydrite in commercial diffusive gradient in thin films (DGT®). The fertilizer was evaluated by a greenhouse experiment using the conventional diffusion method with a plant as an indicator. Samples of fertilizer (monoammonium phosphate, MAP) coated with polyurethane resin from 2 up to 8% by mass were obtained and presented good adhesion to the surface of the synthesized granules. The release rate was assessed by planting ryegrass (Lolium perenne) followed by palisade grass (Urochloa brizantha cv. Piatã) as extractors of available P. Characteristic slow release nutrient absorption profiles were obtained with the addition of MAP coated with polyurethane resin at 8.0% by weight, and opposite profiles, with faster and prompt release for plants, with the addition of uncoated MAP and with coatings from same resin, but with smaller thickness and lower quality of surface coating of the granules. It is noteworthy that for the studied cultures, a mixture of MAP fertilizers with coatings at 0 (without coating) and 8% in equal parts of P met the nutritional needs of the plants, with balanced growth and dry matter yield being observed throughout the experiment.